2010
DOI: 10.1128/cvi.00425-09
|View full text |Cite
|
Sign up to set email alerts
|

Positive Deamidated Gliadin Peptide Antibodies and Negative Tissue Transglutaminase IgA Antibodies in a Pediatric Population: To Biopsy or Not To Biopsy

Abstract: Reports from our clinical laboratory database show that 75% of children <2 years old tested for celiac serology who were found positive for deamidated gliadin peptide (DGP) antibodies had negative results for tissue transglutaminase IgA. DGP levels were shown to decline and disappear without a gluten-free diet. This observation questions DGP's specificity for diagnosis of celiac disease.Celiac serology tests are the necessary tool for correctly referring individuals for duodenal biopsies when diagnosing celiac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 19 publications
(9 reference statements)
1
13
0
1
Order By: Relevance
“…In the study by Olen and colleagues, [ 43 ] villous atrophy was found only in 8 of 149 children with DGP-positivity and tTG-negativity. These findings would suggest duodenal biopsy may be indicated in infants with sole anti-DGP positivity only if they have signs/symptoms consistent with CD and positivity for HLA DQ2/DQ8, as was the case in our patient [ 42 , 44 ].…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…In the study by Olen and colleagues, [ 43 ] villous atrophy was found only in 8 of 149 children with DGP-positivity and tTG-negativity. These findings would suggest duodenal biopsy may be indicated in infants with sole anti-DGP positivity only if they have signs/symptoms consistent with CD and positivity for HLA DQ2/DQ8, as was the case in our patient [ 42 , 44 ].…”
Section: Discussionsupporting
confidence: 61%
“…The positivity of serum anti-DGPs only in very young children has a poor positive predictive value for CD and should be considered with caution: in a retrospective analysis, Parizade found that over 60% of children under 2 years of age with DGP-positive/tTG-negative pattern (HLA alleles not reported) became seronegative within 1 year, without following a gluten-free diet [ 42 ]. In that study, 6 out of 12 children with only anti-DGP positivity referred for biopsy, had a diagnosis of CD [ 42 ]. In the study by Olen and colleagues, [ 43 ] villous atrophy was found only in 8 of 149 children with DGP-positivity and tTG-negativity.…”
Section: Discussionmentioning
confidence: 99%
“…Previous reports have indicated that positive serology can precede small intestinal mucosal atrophy indicating that children with positive EMA have a high probability of having CD, irrespective of negative biopsy [31][32][33]. On the other hand, some authors found that positive antibodies in young children decline over time without treatment with a gluten free diet, especially DGP serology [20,30,34]. In our cohort, a high percentage (77.8%) of patients with normal biopsy was positive for DGP only.…”
Section: Discussionmentioning
confidence: 41%
“…In this study sensitivities and specificities were 100% using 2 different IgG-DGP ELISA kits [ 81 ]. However, since it has been reported that some anti-DGP antibody positive children that are <2 years old became DGP antibody negative over time without maintaining a gluten-free diet, serological follow-up is recommended in this group of patients [ 101 ]. In general, due to the fact that performance of all CD-specific serology tests depends on the prevalence of the condition, the age of the subjects evaluated, and the amount of gluten ingested, these factors should be considered when interpreting CD-specific serology results.…”
Section: Laboratory Tests For CD Diagnosismentioning
confidence: 99%